Examining loyalty of social media influencers: The effects of self-disclosure and credibility - Kaukab Abid Azhar; Che Aniza Che Wel; Siti Ngayesah Ab Hamid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This paper examines the mechanism by which followers become loyal to social media influencers. The study proposes that self-disclosure is a distinct element of influencer brands and has a positive effect on credibility, emotional attachment, and brand trust. A cross-sectional study was designed in which 341 social media users participated. Structural equation modelling (AMOS 22), was used to examine the relationships between variables. Results showed that self-disclosure had a positive relationship with credibility and emotional attachment while the brand trust was increased due to their credibility. Furthermore, it provided evidence of how emotional attachment toward the influencer's brand led to loyalty towards influencer brand through trust. This study is pioneering attempt as it conceptualized the influencer brand's self-disclosures and establishes a link between influencer credibility and followers' conception of their brand. The findings offer valuable insights into developing effective influencer marketing strategies and enhancing influencer brand equity.
Keywords: 330; Social media influencers; self-disclosure; influencers' credibility; social; penetration theory; brand trust; emotional attachment; influencer marketing